EFFECT OF ROUGHNESS ON THE CHARACTERISTICS OF THE HYDRAULIC JUMP EVOLVING INTO A RECTANGULAR CHANNEL OF COMPOUND SECTION - Ghomri, A li; Lacheheb, S ena; Djamaa, W alid (university of el oued/جامعة الوادي, 2022)
T he hydraulic jump is a phenomenon which characterizes the flow in the open channels. It can occur in the channels with rough beds making it p ossi ble to dissipate the significant kinetic energy. this work will analyze this kind of hydraulic jump producing in rough major beds for rectangular channels of compound section. the parameters influencing the length of the jump have been systematically s tudi ed . the analyzes of the phenomenon were conducted using the genera l jump equation. the experimental data were carried out with the aim of establishing dimensional empirical approaches which vary according to the roughness imposed on the major bed. the s e ad ditional approaches obtained are proposed. The results obtained sh owed that the rough major beds can be used to dissipate the hydraulic energies of the hydraulic jump that occurs in the stilling basins.
Article
Keywords: hydraulic jump, open channel, compound sect ion channel, buffer basin, roughness